Pengaruh Modal Intelektual dan DPK Terhadap Manajemen Laba dengan ROA sebagai Variabel Intervening - Hermanto Hermanto; Isdwi Yanti (Jurnal Riset Akuntansi dan Keuangan, 2023)
The purpose of this study is to determine the determinants of earnings management such as intellectual capital, third party funds mediated by Return on Assets (ROA). This study utilizes information taken from the financial reports of banks listed on the IDX by using a purposive sampling test method that meets the exploration steps. The research period is taken for 5 years with the amount of information used is 120 data from 24 banking sub-sector entities. The research method uses Partial Least Square (PLS) with secondary data types. The results of the study show that there is a partially positive influence of intellectual capital and third party funds on return on assets, there is a positive relationship between intellectual capital and earnings management, and there is no relationship between third party funds on earnings management, and there is a negative effect of return on assets on management. profit. Return on assets is able to mediate intellectual capital on earnings management and return on assets is not able to mediate the relationship of third party funds on earnings management.